2014
DOI: 10.1103/physreve.89.052501
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal alignment induced by micron-scale patterned surfaces

Abstract: Induced bulk orientation of nematic liquid crystal in contact with micron-scale patterned surfaces is investigated using the Landau-de Gennes theory by means of three-dimensional simulations. The effect of the size and spacing of square cross-sectional well and post patterns is investigated and shown to influence the orientation of the liquid crystal bulk, far removed from the surface. Additionally, the effective anchoring strength of the induced alignment is estimated using a modified version of the torque ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…We investigated LC droplets confined in spherical shells using both continuum and molecular approaches. At the continuum level, using the finite-element method, 30,32,33 we obtained a clear map of the defects within the droplet as a function of surface anchoring conditions. For these calculations the droplets are 0.1 μm in diameter and the LC mesogens are described by a Q-tensor field, therefore losing, in part, their chemical identity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated LC droplets confined in spherical shells using both continuum and molecular approaches. At the continuum level, using the finite-element method, 30,32,33 we obtained a clear map of the defects within the droplet as a function of surface anchoring conditions. For these calculations the droplets are 0.1 μm in diameter and the LC mesogens are described by a Q-tensor field, therefore losing, in part, their chemical identity.…”
Section: Resultsmentioning
confidence: 99%
“…For F B and F D calculations, the chosen parameters correspond to 5CB. 33 For F S calculations, we defined two surfaces that impose strong planar degenerate or strong homeotropic anchoring. 31 Strong anchoring conditions are defined as boundary conditions and do not contribute directly to the free energy.…”
Section: Q-tensor Simulationsmentioning
confidence: 99%
“…This places several constraints on the nanostructure dimensions and constituent materials. It has been shown that the orientation of LC on a nanostructured surface is highly dependent on the space in which it is confined 24 25 26 , that is, if the well depth-to-diameter ratio is too large, the LC aligns vertically (homeotropic alignment) inside the well 27 . For this reason, the nanowells must be shallow to allow the homogeneous alignment of the LC inside.…”
Section: Resultsmentioning
confidence: 99%
“…Th e orientation of LC molecules depends on Van der Waalse intermolecular forces and an anisotropic elastic interaction at interfaces with a solid surface [7]. Modern techniques of preparing thin solid fi lms allow to control a pretilt angle and LC molecules alignment by changing a surface morphology and physicochemical properties [8][9][10][11][12][13]. Previous studies established that the orientation of LC molecules on metals surfaces depends on the properties of these materials, thickness of metal fi lms and morphology of metal fi lm surfaces.…”
Section: Introductionmentioning
confidence: 99%